Synthesis of Isatins through Direct Oxidation of Indoles with IBX-SO3K/NaI - Bredenkamp, Angla; Mohr, Fabian; Kirsch, Stefan F. (Synthesis, 2015)
The direct conversion of indoles into isatins is presented. The reagent mixture NaI/IBX-SO3K, containing a sulfonylated derivative of 2-iodoxybenzoic acid, was employed to trigger this oxidative process. Moreover, the synthetic route toward IBX-SO3K and the X-ray crystal structure of the title compound are described in great detail.
Keywords: hypervalent iodine; oxidation; indoles; isatins; heterocycles